EFEKTIVITAS VIDEO EDUKASI TENTANG ANEMIA TERHADAP PENGETAHUAN IBU HAMIL DALAM MENCEGAH ANEMIA DI PUSKESMAS ABANG 1 KARANGASEM - Putu Adi Cahya Dewi; I Nyoman Windhu Paramarta; I Nyoman Suartha (Jurnal Medicare, 2025)
Anemia in pregnancy can adversely affect maternal and fetal mortality and morbidity. Lack of knowledge of pregnant women about preventing anemia is one of the factors that cause the high incidence of anemia in pregnancy. The purpose of this study was to determine the effectiveness of educational videos on pregnancy anemia on the knowledge of pregnant women in preventing anemia. The research method was Pre-Experimental One-Group Pretest-Postest Design. The research sample was pregnant women in the first, second and third trimesters who were recorded visiting the MCH Poli of Puskesmas 1 Abang Karangasem who met the sample criteria of 20 people selected by purposive sampling technique. Data were collected with knowledge and attitude questionnaires. Data were analyzed by the Wilcoxon Signed Rank Test statistical test. The results showed that the mother's knowledge in preventing anemia increased after the provision of educational videos, where statistically educational videos on pregnancy anemia were effective on the knowledge of pregnant women in preventing anemia (p value = <0.001; α = 0.05). Suggestions to health workers to improve the provision of education and information to pregnant women about anemia in pregnancy through the use of educational media tailored to technology and counseling targets.